Efeitos do manto de intemperismo sobre anomalias eletromagnéticas provocadas por corpos tabulares inclinados: um estudo através de modelamento reduzido - SILVA, Lúcia Maria da Costa e (Universidade Federal do Pará, 2014)
Electromagnetic methods have been extensively applied in the prospecting of sulphide bodies and other conducting materials. The interpretation of e. m. data is based on the results obtained either with reduced scale or analytical modelling. In most models, the host rocks, the overburden as well as the halo of disseminated sulphides are considered highly resistive although in nature they are often weakly conductive. Presence of a well-developed conducting overburden in tropical and sub-tropical regions and a saline rich crustal layer in semi-arid regions have been found to modify significantly the e. m. anomalies in practice. Therefore, the parameters of the target, determined on the basis of simple models where the presence of the conducting environment is neglected, are found to be in considerable error. The effects of the overburden on the e. m. anomalies of a dipping tabular ore body were studied with reduced scale models for varying response parameters of both the overburden and the orebody, and also for different depths and dips of the target. The overburden and the orebody were represented by metallic sheets of varying thickness in the scale model developed in accordance with the law of electromagnetic similitude. The results of these investigations show that the overburden affects the anomaly by causing: a) phase rotation; b) amplitude reduction; c) base level displacement; d) reversion of the quadrature; and e) appearance of an extra peak in the quadrature in the case of low dipping models. The last two effects complicate the quantification of the anomalies but, on the other hand, provide a qualitative indication of the response parameters of both the ore body and the overburden. The results were assembled in the form of Argand diagrams and, finally, an interpretation scheme is suggested for the e. m. field data on the basis of these diagrams.